VISITOR BEHAVIOR AT THEME PARKS AS AN URBAN TOURISM IN THE CITY OF BANDUNG, INDONESIA - Ersy Ervina; Vany Octaviany (Institut Pariwisata dan Bisnis Internasional, 2016)
The presence of a variety of theme parks in Bandung, Indonesia is intended as an urban tourism and public green spaces whereby the townspeople can make interactions. In reality, there are many visitors who still not realize the purpose and function of the theme parks. Some of the newly constructed parks are damaged by visitor behavior. This condition makes the theme park less comfortable. This study was aimed to identify and analyze of visitor behavior at the Bandung theme parks as urban tourism.This study used quantitative descriptive analysis technique by tabulating the frequency responses of respondents. Visitor behavior was analyzed using two (2) sub variables, including personal and interpersonal factors. Personal factors consist of six indicators, i.e. (1) need, want and motivation; (2) perception; (3) learning; (4) personality; (5) lifestyle; and (6) self-concept. Meanwhile, interpersonal factors consist of five indicators, i.e. (1) culture; (2) reference group; (3) social class; (4) opinion leader; and (5) family. The analysis results show that the visitor behavior at theme parks as urban tourism, analyzed by personal and interpersonal factors, is in sufficient condition (not yet positive). On the personal factors, the highest indicator is need, want and motivation and the lowest indicator is personality. On interpersonal factors, the highest indicator is opinion leader. Therefore, it is necessary to enhance socialization in order to increase the knowledge of visitors pertaining to the function of theme parks and to amke proper regulations regarding superintendence of theme parks.